Assessment of maternal morbidity and mortality in HELLP syndrome in a referral maternity hospital in Piauí (Research, Society and Development, 2022)
Introduction: HELLP syndrome in pregnancy is characterized by hemolysis, alteration of liver enzymes and thrombocytopenia, putting the pregnant woman and fetus at risk. Objective: To analyze maternal morbidity and mortality due to HELLP Syndrome in a referral hospital in Piauí. Methodology: The scope was developed through a retrospective analysis of medical records of pregnant and postpartum women from an Intensive Care Unit (ICU) of a public referral maternity hospital in the city of Teresina, Piauí, with a diagnosis of HELLP Syndrome, between January 2016 to December 2018. The study included the quantification of the most used mode of delivery for termination of pregnancy and the number of patients in which terminations of pregnancy occurred, data recorded in Microsoft Excel®. Descriptive statistics were calculated: mean, standard deviation, minimum and maximum, for quantitative variables; and frequencies, for qualitative variables. In the inferential analysis, the Kolmogorov-Smirnov and Student's t tests were used to verify normality and comparison between groups, respectively, in addition, for qualitative independent variables, Pearson's chi-square was performed. Results: From a total of 68, 45.6% (31) of the women had at least one maternal complication. Six (8.8%) maternal deaths were identified. The most prevalent complications were acute respiratory failure 10 (14.7%), acute renal failure 10 (14.7%), infection 10 (14.7%), placental abruption 9 (13.2%), coagulation 7 (10.3%) and 14 (20.6%) presented near miss aspects. Conclusion: The morbidity of pregnant and postpartum women admitted to the ICU of the aforementioned maternity hospital with a diagnosis of HELLP syndrome was high.